2016
DOI: 10.1016/j.matchar.2016.05.010
|View full text |Cite
|
Sign up to set email alerts
|

X-ray tomography studies on porosity and particle size distribution in cast in-situ Al-Cu-TiB2 semi-solid forged composites

Abstract: . (2016) X-ray tomography studies on porosity and particle size distribution in cast in-situ Al-Cu-TiB2 semi-solid forged composites. Materials Characterization. Permanent WRAP URL:http://wrap.warwick.ac.uk/79069 Copyright and reuse:The Warwick Research Archive Portal (WRAP) makes this work by researchers of the University of Warwick available open access under the following conditions. Copyright © and all moral rights to the version of the paper presented here belong to the individual author(s) and/or other c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…The possible reason for this could be the better distribution of TiB 2 particles and reduction in cluster size when subjected to 30% deformation [49]. The cluster size reduction and TiB 2 particle distribution in Al-4.5Cu-5TiB 2 composite with 30% reduction by semisolid forging was well explained in our recent X-ray computed tomography studies [28]. Kuruvilla et al [50] found that the extremely fine size TiB 2 particle reinforcements results in the improvement of elastic modulus of the aluminium matrix composite.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 61%
See 1 more Smart Citation
“…The possible reason for this could be the better distribution of TiB 2 particles and reduction in cluster size when subjected to 30% deformation [49]. The cluster size reduction and TiB 2 particle distribution in Al-4.5Cu-5TiB 2 composite with 30% reduction by semisolid forging was well explained in our recent X-ray computed tomography studies [28]. Kuruvilla et al [50] found that the extremely fine size TiB 2 particle reinforcements results in the improvement of elastic modulus of the aluminium matrix composite.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 61%
“…Recent X-ray computed tomography studies on Al-4.5%Cu-5%TiB 2 in-situ composite showed that semisolid forging has resulted in improvement of TiB 2 particle size distribution and reduction of particle clusters [28]. Additionally, Deepak Kumar et al [29], suggested that semisolid forging of Al-5TiB 2 composites improves mechanical properties of the composite.…”
Section: Introductionmentioning
confidence: 99%
“…95 It is generally believed that the presence of a Al 3 Ti phase in Al/TiB 2 composites is beneficial for grain refinement but is detrimental to the mechanical properties. 96 The Al 3 Ti can be eliminated during synthesis by the proper control of temperature, time, and ratios of the raw materials. 91,97 The presence of Si in cast Al alloys can improve the dispersion of TiB 2 particles, 98 although the TiB 2 particles are still partially segregated in the eutectic regions because of the pushing mechanism during solidification.…”
Section: Al/tib 2 Compositesmentioning
confidence: 99%
“…Tham et al [21] believed that processing-induced voids were eliminated by highly compressive hydrostatic stresses generated during high deformation degrees. However, Matthew et al [10] have observed that after a certain deformation degree, the quantity of porosity and clustering was slightly increased. Also, Shi et al [22] found that an increase in the degree of forging deformation from 40 % to 60 % caused enhanced localized strain and matrix hardening resulting in the matrix inability to easily squeeze into the voids and subsequent creation of new types of voids.…”
Section: Introductionmentioning
confidence: 99%
“…Sharifian [8] and Mousavian [9] have reported significant fragmentation of particles after the extrusion. The studies conducted by Matthew et al [10] indicated that 30 % forging reduction led to a greater uniformity of distribution of reinforcing particles compared to the ascast composite. It was also found that hot extrusion reduced the porosity and increased the interfacial bonding strength [11 -13].…”
Section: Introductionmentioning
confidence: 99%